Storythat Comic Based on the Ngideri Dhisah Tradition to Enhance Students’ Visual Perceptual Skills - Triyanto, Jefri Rieski; Na’im, Mohamad (Universitas Negeri Padang, 2024)
This study aims to develop a history learning medium using a Storythat comic based on the Ngideri Dhisah tradition. Secondly, it aims to measure the effectiveness of the Storythat comic medium based on the Ngideri Dhisah tradition in enhancing students’ visual perceptual skills. This research is a development study or Research & Development (R&D) adopting the ADDIE model by Branch. The study was conducted at SMAN 1 Tenggarang with the research subjects being grade X students. Data collection techniques included questionnaires, interviews, and observations. Meanwhile, the data analysis technique to measure students’ visual perceptual skills used IBM SPSS V29. The results of this study indicate that: (1) the Storythat comic medium based on the Ngideri Dhisah tradition is suitable for use in the learning process with minor revisions; (2) the Storythat comic medium based on the Ngideri Dhisah tradition can significantly enhance students’ visual perceptual skills with a “Large Effect” category (Relative Effectiveness Test score of 0.83). This research provides initial information for future studies that will examine the effectiveness of the Storythat comic medium in improving students’ visual perceptual skills, particularly in the history learning process.